2015
DOI: 10.1016/s0924-9338(15)30429-6
|View full text |Cite
|
Sign up to set email alerts
|

Lower Estimated Glomerular Filtration Rates in Patients On Long Term Lithium; a Comparative Study and a Meta-analysis of Literature

Abstract: Background: Several studies have shown that long-term lithium use is associated with a subtle decline in estimated glomerular filtration rate. This study compared mean estimated glomerular filtration rates (eGFR) in patients on long term lithium, against matched controls. Methods: Patients with bipolar affective disorder, who are on lithium (for at least a year), were compared against controls that were matched (1:1) for age, gender and presence or absence of diabetes or hypertension. The eGFR was calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
4
1
1
Order By: Relevance
“…However, numerous studies have reported a deterioration of renal function in older adults with longer use of lithium therapy (36,(62)(63)(64)(65). The annual decrease of GFR is estimated at 2.3 ml/min/1.73m 2 in this population (66).…”
Section: Discussionmentioning
confidence: 93%
“…However, numerous studies have reported a deterioration of renal function in older adults with longer use of lithium therapy (36,(62)(63)(64)(65). The annual decrease of GFR is estimated at 2.3 ml/min/1.73m 2 in this population (66).…”
Section: Discussionmentioning
confidence: 93%
“…Apart from advanced age, duration of lithium treatment is an added risk factor for reduced glomerular filtration rate (GFR) and the subsequent deterioration of renal function 10. Studies showed that patients on long-term lithium had significantly lower GFR values11 and renal failure tends to ‘appear after decades of treatment and gradually progresses irrespective of lithium continuation’ 12. Nephrogenic diabetes insipidus, tubulointerstitial nephritis and nephrotic syndrome are among the manifestations of lithium nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…раздел 2.1). Другие факторы риска, которые необходимо учитывать в данной группе пациентов, -это эректильная дисфункция и гиперпролактинемия, которая носит вторичный характер при антипсихотической фармакотерапии (83,84), а также хроническое поражение почек как побочное действие литиумной профилактики (85). Эти независимые факторы риска ССЗ являются следствием лечения, назначаемого по поводу психоза, что может значительно повышать сердечно-сосудистый риск.…”
Section: ссз и тяжелые психические расстройстваunclassified